Immunogenicity of SCB-2019 Coronavirus Disease 2019 Vaccine Compared With 4 Approved Vaccines. (19th November 2021) - Ambrosino, Donna; Han, Htay Htay; Hu, Branda; Liang, Joshua; Clemens, Ralf; Johnson, Marina; Siber, George; Goldblatt, David
Abstract: A significant correlation has been shown between the binding antibody responses against original severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein and vaccine efficacy of 4 approved coronavirus disease 2019 vaccines. We therefore assessed the immune response against original SARS-CoV-2 elicited by the adjuvanted S-Trimer vaccine, SCB-2019 + CpG/alum, in the same assay and laboratory. Responses to SCB-2019 were comparable or superior for antibody to original and Alpha variant when compared with 4 approved vaccines. The comparison accurately predicted success of the recently reported efficacy trial of SCB-2019 vaccine. Immunogenicity comparisons to original strain and variants of concern should be considered as a basis for authorization of vaccines. Abstract : The antibody-binding responses to the adjuvanted S-Trimer vaccine, SCB-2019 + CpG/alum, were compared with approved vaccines and accurately predicted success of the recently reported efficacy trial of SCB-2019 vaccine. Immunogenicity comparisons should be considered as a basis for authorization of vaccines.